A "SEMIOLOGICAL TURN" IN PEDAGOGICAL SCIENCES - A. A. Polonnikov (Высшее образование в России)
The main issue discussed in the paper concerns the conditions and effects of reification (objectification) of the humanities realities produced by a scholarly-pedagogical text. A physicalist scholarly orientation towards realization o fthe "truth regime" is being considered as one ofthe main reifying conditions. Dereification is related to the "semiological turn" of the scholarly-pedagogical statement determined by self-referentiality of the scholarly-pedagogical language and communicative objectivization of its rhetorical forms. Another condition for dereification is a change of the scientificity image that educational sciences are oriented at.